Analysis of Sulfamethoxazole and Trimethoprim Content in Novatrim Tablets Using Ultraviolet Spectrophotometry - Wijiyaningsih, Dinda; Agustina, Sry (PCJN: Pharmaceutical and Clinical Journal of Nusantara, 2023)
The accurate quantification of fixed-dose combination antibiotics is critical for ensuring therapeutic safety and efficacy. This study determined the content of sulfamethoxazole (SMX) and trimethoprim (TMP) in Novatrim tablets using the UV multicomponent spectrophotometric simultaneous equation method with phosphate buffer pH 7 as solvent. Maximum wavelengths were established at 270 nm (SMX) and 275 nm (TMP). Absorptivity constants determined were: a¹SMX = 0.2601, a²SMX = 0.2113, a¹TMP = 0.2170, a²TMP = 0.1721 (mL·µg⁻¹·cm⁻¹). Six replicate analyses of Novatrim tablets yielded SMX contents of 3.12%–40.39% and TMP contents of 1.92%–76.16%, both below the Farmakope Indonesia VI acceptance criterion of 93.0%–107.0%. The structural basis for UV detection was elucidated: SMX absorbs through a benzene–SO₂–isoxazole conjugated chromophore with a para-aminophenyl auxochrome (–NH₂); TMP absorbs through a diaminopyrimidine–trimethoxybenzyl chromophore system with –NH₂ and –OCH₃ auxochromes. Subthreshold recoveries were primarily attributed to reference standard degradation compromising chromophore and auxochrome integrity, compounded by out-of-range absorbance measurements and high spectral overlap between the two analytes. This study highlights the critical importance of reference standard storage conditions in multicomponent UV spectrophotometric analysis.